On the State of the (Im)possible: Notes on Wael Hallaq's Thesis - Ahmad, Irfan (Journal of religious and political practice, 2015)
This essay offers some critical reflections on Hallaq's (2013) The Impossible State. In part I, I summarize the author's contention. Part II identifies certain conceptual tensions in and neglect of some of the issues therein. I dwell in particular on three aspects: (a) the meanings of sharia, its place in Islam and its usage in the academic discourses; (b) the possibility of disentangling the calls for an Islamic state from statism to stress other forms of politics; and (c) the retrieval of initiatives and thoughts counter to nationalism. I stress the aligning of the philosophical with lifeworld in such a manner that one does not subsume the other. Briefly I also examine orientalism and its unwitting traces even in critiques of orientalism. I end by discussing "aspectualism" in anthropological writings on the state and ask if aspectualism is inherent in scholarly enterprise. This essay by an anthropologist (also trained in sociology and political science) on the work of an expert of Islamic law, I hope, will contribute to interdisciplinary discussions on themes that Hallaq's important book, with its sharp thesis, has raised.